Profesionalisme TNI di tengah Transisi Politik - J. Kristiadi (Antropologi Indonesia, 2001)
The Indonesian Armed Force (Tentara Nasional Indonesia, TNI) has for decades been the instrument used by those in power to endorse and hold their powerful positions. As a consequence, the Indonesian Armed Force has not only lost its professionalism, but also its quality and competence. A professional army can only be established in the condition of a democratic political life. In this article the author describes the situation in Indonesia nowadays, i.e. the transition towards democratization. In this process, the most important agenda is to return the main function of the Indonesian Armed Force in line with the need and the will of Indonesian people, i.e. to guard the nation sovereignty and territory. However, the author also recognizes the other functions the armed force has to carry out. In relation to this, the article examines how the professionalism of the Indonesian Armed Force can be formed in the midst of a political transition process. The author proposes several steps to be taken, i.e. to revise or replace the legislation about the state's defense policy; revise the armed force's doctrine so as to accommodate the people's needs; revise the legislation on the police force to enable the police to guard the civil order, strengthen the law, and avoid the outside intervention; as well as to allow the armed force's members to choose their representatives in the general election.